Policy transformation in Canada: Is the past prologue? - Carolyn Hughes Tuohy; Sophie Borwein; Peter John Loewen; Andrew Potter (University of Toronto Press, 2019)
Canada's centennial anniversary in 1967 coincided with a period of transformative public policymaking. This period saw the establishment of the modern welfare state, as well as significant growth in the area of cultural diversity, including multiculturalism and bilingualism. Meanwhile, the rising commitment to the protection of individual and collective rights was captured in the project of a "just society." Tracing the past, present, and future of Canadian policymaking, Policy Transformation in Canada examines the country's current and most critical challenges: the renewal of the federation, managing diversity, Canada's relations with Indigenous peoples, the environment, intergenerational equity, global economic integration, and Canada's role in the world. Scrutinizing various public policy issues through the prism of Canada's sesquicentennial, the contributors consider the transformation of policy and present an accessible portrait of how the Canadian view of policymaking has been reshaped, and where it may be heading in the next fifty years.
hdl:1807/94443
Keywords: 330; economics; Canadian history; public policy and administration; social policy; Canadian politics; political history; political science; sociology; history